A Review of Medicinal Uses, Phytochemistry and Biological Activities of Markhamia tomentosa - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Markhamia tomentosa (Benth.) K. Schum. ex Engl. is a shrub or small tree widely used as traditional medicine throughout its distributional range in west Africa. This study was aimed at providing a critical review of medicinal uses, phytochemistry and biological activities of M. tomentosa. Documented information on medicinal uses, phytochemistry and biological activities of M. tomentosa was collected from several online sources such as Scopus, Google Scholar, PubMed and Science Direct, and pre-electronic sources such as book chapters, books, journal articles and scientific publications obtained from the University library. This study revealed that the bark, leaf, root and stem bark decoction and/or infusion of M. tomentosa are mainly used as traditional medicine for elephantiasis, infertility, skin infections, rheumatism, eye problems, pain, diabetes and fever. Phytochemical compounds identified from the species include alkaloids, anthraquinones, cardiac glycosides, flavonoids, phenolics, saponins, sterols, tannins and triterpenoids. Markhamia tomentosa crude extracts and compounds isolated from the species exhibited analgesic, acetylcholinesterase and butyrylcholinesterase inhibitory, anti-amnesic, antibacterial, antifungal, antifeedant, anti-inflammatory, antioxidant, antiplasmodial, antitrypanosomal, antiulcer, larvicidal, leishmanicidal and cytotoxicity activities. Markhamia tomentosa should be subjected to detailed phytochemical, pharmacological and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological activities.